Manuscripts of the Book of Revelation new philology, paratexts, reception - Allen, Garrick V. 1988- (Oxford University Press, 2020)
The book of Revelation is a disorienting work, full of beasts, heavenly journeys, holy war, the End of the Age, and the New Jerusalem. It is difficult to follow the thread that ties the visions together and to makes sense of the work's message. This book argues that one way to understand the strange history of Revelation and its challenging texts is to go back to its manuscripts. The texts of the Greek manuscripts of Revelation are the foundation for the words that we encounter when we read Revelation in a modern Bible. But the manuscripts also tell us what other ancient, medieval, and early modern people thought about the work they copied and read. The paratexts of Revelation-the many features of the manuscripts that help readers to navigate and interpret the text-are one important point of evidence
Keywords: Bibel -- Offenbarung des Johannes; Textgeschichte; Handschrift; Paratext; Bible / Revelation / Criticism, interpretation, etc; Bible / Revelation